PRE-STRAIN EFFECT EVALUATION OF AUSTENITIC STAINLESS STEEL - LIU XiaoNing; YANG Fan; LIU Cen; WU YuanXiang; LIU Bing; ZHANG HongWei (Jixie qiangdu)
Pre-strain on austenitic stainless steel was a method in order to obtain good mechanical properties,the pre-strain effect evaluation was the basis of improving the production process of the steel. Applying the theory of probability and mathematical statistics,the evaluation system of pre-strain effect was established: the pre-strain effect on the mechanical properties parameter standard deviation was evaluated,using F-distribution; the pre-strain effect on the mechanical properties parameter mean value was evaluate,using t-distribution. For example of pre-strain effect on austenitic stainless steel S30408,based on the effective tensile test data at liquid nitrogen temperature,and the bilateral confidence was 99%,the effect of 9%-prestrain on the steel was evaluated: 1) 9%-pre-strain significantly increases the yield strength of steel S30408,and the standard deviation is basically unchanged; 2) for steel S30408 tensile strength,9%-pre-strain is no effect on the mean and the standard deviation.